Micro- and nanoparticles for treating cardiovascular disease. (17th February 2015) - Suarez, S.; Almutairi, A.; Christman, K. L.
Abstract : Micro- and nano-particles are being designed as delivery vehicles to provide a sustained therapeutic stimulus at the injured tissue. Abstract : Cardiovascular disease, including myocardial infarction (MI) and peripheral artery disease (PAD), afflicts millions of people in Unites States. Current therapies are insufficient to restore blood flow and repair the injured heart or skeletal muscle, respectively, which is subjected to ischemic damage following vessel occlusion. Micro- and nano-particles are being designed as delivery vehicles for growth factors, enzymes and/or small molecules to provide a sustained therapeutic stimulus at the injured tissue. Depending on the formulation, the particles can be injected directly into the heart or skeletal muscle, or accumulate at the site of injury following an intravenous injection. In this article we review existing particle based therapies for treating MI and PAD.